2011
DOI: 10.2341/10-221-l
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and Abrasive Wear of Nano Restorative Materials

Abstract: Clinical Relevance Some nanofilled restorative materials may provide superior resistance to biomechanical degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 31 publications
2
40
0
4
Order By: Relevance
“…11 In this current study, these characteristics contributed to the abrasion resistance of Ketac N100, which was not statistically significantly different from that of the nanocomposite (Table 2). Similar results were found by de Paula and others, 17 in whose study the surface roughness of Ketac N100 did not differ from that of a nanocomposite after biomechanical degradation. However, the larger and irregular filler particles present in Vitremer and Fuji IX GP ( Figure 1C,F) made it easier to ''pluck out'' a whole filler particle from the resin matrix, which could act as an additional abrasive agent once it has detached from the surface and is held against the specimen.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…11 In this current study, these characteristics contributed to the abrasion resistance of Ketac N100, which was not statistically significantly different from that of the nanocomposite (Table 2). Similar results were found by de Paula and others, 17 in whose study the surface roughness of Ketac N100 did not differ from that of a nanocomposite after biomechanical degradation. However, the larger and irregular filler particles present in Vitremer and Fuji IX GP ( Figure 1C,F) made it easier to ''pluck out'' a whole filler particle from the resin matrix, which could act as an additional abrasive agent once it has detached from the surface and is held against the specimen.…”
Section: Discussionsupporting
confidence: 79%
“…15,16 Laboratory studies assess the surface integrity of restorative materials using mechanical degradation tests, such as wear simulation and brushing abrasion, which evaluate the surface texture and wear/ abrasion resistance of materials. [17][18][19][20] Corrosive wear or mechanical degradation results from the joint action of chemical and mechanical forces and is also associated with the mechanical removal of corroded layers that form on the surface of a material through a reaction with its environment. 21 However, it is also important to determine how the surface of restorative materials performs as a consequence of the chemical degradation that also occurs in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…56, No. 1, [11][12][13][14][15][16]2014 Original Physicomechanical properties of a zinc-reinforced glass ionomer restorative material material (ChemFil Rock, Dentsply Caulk) was recently introduced to improve flexural strength (6), hardness, wear resistance, and fracture toughness. However, few studies have evaluated these properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed a direct correlation between the size of the filler and the amount of material loss [5,6]. The shape of the fillers can also influence the resistance of the composite resin to abrasive challenge.…”
Section: Introductionmentioning
confidence: 99%